Interlayer composite PET foam capable of improving flame retardant property as well as preparation method and application of interlayer composite PET foam
By using the composite structure of the top layer, the PET composite interlayer and the anti-seepage bottom layer in the interlayer composite PET foam, the flame retardant performance is improved by using nanomaterials and flame retardant, the problem of insufficient flame retardant performance of existing PET foam is solved, and higher fire safety and service life are achieved.
Patent Information
- Application Number
- CN202411667831.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-08
AI Technical Summary
The flame retardant performance of existing interlayer composite PET foams is insufficient, making it difficult to meet safety requirements in harsh environments such as ships and wind turbines. At the same time, the addition of flame retardant additives will affect the mechanical properties of the material.
The interlayer composite PET foam is used, which is composed of the top layer, the PET composite interlayer and the anti-seepage bottom layer by hot pressing. The top layer is composed of layered nanocarbon black and aluminum hydroxide solution. Zinc borate and expanded graphite are added as flame retardant to the PET composite interlayer. The anti-seepage bottom layer is composed of materials such as rosin, redispersible latex powder and tourmaline powder.
The flame retardant properties of the material are significantly improved, and a protective layer and a heat insulation layer are formed to inhibit the spread of flames, and the moisture penetration is prevented through the anti-seepage bottom layer, extending the service life of the material.
Smart Images

Figure BDA0005145043040000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PET foam preparation, in particular to a sandwich composite PET foam with improved flame retardancy and a preparation method and application thereof. Background Art
[0002] Sandwich composite PET foam is a lightweight, closed-cell thermoplastic foam material made of polyethylene terephthalate (PET). It is usually used as the core material of sandwich structures of composite materials. Because of its good shear, compression and high temperature resistance, it is widely used in construction, road transportation, rail transportation, aviation, wind power and other fields.
[0003] The flame retardant properties of PET foam can improve the thermal stability of PET foam, effectively slow down the spread of fire, reduce the risk of fire, and reduce safety hazards. Common flame retardant additives include halogen, phosphorus and silicon. Among them, although halogen flame retardants have excellent flame retardant effects, they will release a large amount of toxic and harmful gases when burned. Compared with halogen flame retardants, phosphorus and silicon flame retardants have low smoke, low toxicity, and are green and environmentally friendly, becoming a research hotspot in the field of flame retardant research. However, the addition of flame retardant additives will affect the mechanical properties of the material.
[0004] It is very necessary to improve the flame retardant properties of sandwich composite PET foam, mainly for the following reasons: PET itself is flammable to a certain extent, which can easily cause secondary disasters in emergency situations such as fire. Especially as a necessary material for ships and wind turbines that are exposed to harsh environments for a long time or in the medical field, PET foam composite boards need to meet certain flame retardant standards and have moisture-proof and anti-aging properties to ensure safe use. Improving flame retardant properties can extend the service life of the material and improve the safety and reliability of the product.
[0005] In order to solve the above problems, the present invention proposes a sandwich composite PET foam with improved flame retardancy and a preparation method and application thereof. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a sandwich composite PET foam with improved flame retardancy, and a preparation method and application thereof.
[0007] The technical solution of the present invention is: a sandwich composite PET foam with improved flame retardancy, which is formed by hot pressing and molding a top surface layer, a PET composite sandwich layer and an anti-seepage bottom surface layer from the outside to the inside;
[0008] The top surface layer is compounded by a layered nano carbon black solution with a mass concentration of 35-45%, a layered nano aluminum hydroxide solution with a mass concentration of 96-98%, and a dispersant in a ratio of 1:1:0.3-0.6;
[0009] The PET composite interlayer is formed by a composite layer obtained by compounding a PET resin film and a foam material in equal mass ratios and then undergoing surface anti-reflection treatment; the foam material comprises, by weight: 80 to 100 parts of polyethylene terephthalate, 0.5 to 3 parts of polytetrafluoroethylene, 1 to 5 parts of a flow promoter, 1 to 4 parts of a flame retardant, and 3 to 10 parts of glycerol; the flame retardant is a mixture of zinc borate and expanded graphite in a mass ratio of 1:1;
[0010] The anti-seepage bottom surface layer comprises, by weight: 15 to 20 parts of rosin, 2 to 7 parts of redispersible latex powder, 1 to 5 parts of tourmaline powder, and 25 to 40 parts of ethylene-vinyl acetate copolymer;
[0011] Description: The sandwich composite PET foam proposed in this application is obtained by compounding a top surface layer, a PET composite interlayer and an anti-seepage bottom surface layer. The top surface layer provides a certain mechanical strength and surface protection. The foam interlayer structure without a reflective layer can achieve effective absorption of electromagnetic waves and improve the flame retardant properties of the material. Zinc borate and expanded graphite as flame retardants in the PET composite interlayer can form a protective layer during combustion to isolate oxygen, while releasing non-flammable gas to inhibit the spread of flames, and during thermal decomposition, the expanded graphite will rapidly expand to form an insulation layer, effectively blocking oxygen and heat, thereby improving the flame retardant properties of the material. The setting of the anti-seepage bottom surface layer helps to prevent moisture penetration, thereby protecting the core material from the influence of the humid environment and maintaining the integrity and durability of the structure. In the marine environment or other humid conditions, the intrusion of moisture will have a negative impact on the performance of the composite material, including reducing the mechanical properties and accelerating the aging of the material. By improving the anti-seepage performance of the bottom surface, the service life of the sandwich structure can be effectively extended, especially in applications such as ships and wind turbines that are exposed to harsh environments for a long time.
[0012] Rosin can form a protective layer during the combustion process to slow down the transfer of heat and oxygen, while tourmaline powder will increase the mechanical strength of the composite material, including tensile strength and compressive strength, thereby effectively improving the durability and stability of the anti-seepage bottom layer. Tourmaline powder will also improve the stability of the composite material at different temperatures, which is particularly important for maintaining anti-seepage performance in a changing environment. Redispersible latex powder and ethylene-vinyl acetate copolymer may indirectly affect the flame retardant properties by improving the overall structure of the material.
[0013] Furthermore, the surface anti-reflection treatment method is:
[0014] Preparation of honeycomb inorganic particles: mixing ground nano cerium oxide particles and microalgae solution in a mass ratio of 13-20:8-10 to obtain a composite liquid, then mixing silane and diol in a mass ratio of 7-10:1-4 to obtain a modifier, adding 5-7wt.% of the modifier to the composite liquid at a rate of 25-50mL / min, stirring and hydrolyzing at room temperature for 5-10h, and then casting into a honeycomb gypsum blank with a through-hole diameter of 0.2-5ppi at a pressure of 0.5-1MPa and a pressurizing time of 25-40s, aging at a temperature of 80-100°C for 20-24h, and then removing the gypsum to obtain honeycomb inorganic particles;
[0015] Surface anti-reflection treatment: honeycomb inorganic particles are deposited on the surface of the composite layer, and then low-temperature plasma curing is performed for 50 to 200 seconds under a nitrogen atmosphere at 50 to 90°C to obtain a PET composite interlayer; the flow rate of the honeycomb inorganic particles is 800 to 1000 cm 3 / min, deposition rate is 1.80~3.50g / min, deposition amount is 50~80g / dm 2 ;
[0016] Description: The composite liquid obtained by mixing honeycomb nano cerium oxide particles and microalgae solution, coated on the surface of PET resin film and foam material after alternating composite, can significantly improve the anti-reflection effect of the material. This is because the honeycomb nano cerium oxide particles have a special porous structure, which can effectively scatter light and reduce surface reflection. The microalgae solution may contain specific biomolecules, which can improve the bonding between the particles and the PET foam surface, forming a more uniform and continuous coating, thereby improving the anti-reflection performance, and the biomolecules contained in the microalgae solution can further improve the bonding ability between the particles and the resin surface, thereby enhancing the uniformity and durability of the coating. In addition, in the marine environment, the calcareous layer can promote the attachment of microalgae, and the combined effect of the microalgae and the calcareous layer can protect the base material. Anti-reflection treatment of PET foam surface is usually to create a super-hydrophobic and rough surface, reduce the transmission and absorption of light, and improve reflectivity. Improving reflectivity can reduce heat loss through radiation, thereby enhancing the thermal insulation performance of the material; and anti-reflection treatment for tight instruments in marine environments can also make the PET foam surface more effective in reflecting light or radar signals, which can increase the probability of detection of equipment in the ocean, whether through vision during the day or through radar systems at night or in low visibility;
[0017] The microalgae solution contains biopolymers, which may form a network structure in the composite material, which can further improve the temperature resistance. Silane coupling agents are usually used to improve the interface bonding between inorganic fillers and organic matrices, which may help improve the mechanical properties of composite materials at high temperatures. Diol modifiers affect the temperature resistance of composite materials by changing the molecular structure of PET and interacting with nano-cerium oxide particles and silane coupling agents.
[0018] The hydrolysis and pressure casting steps after the addition of the modifier help embed the modified nano-cerium oxide particles into the honeycomb gypsum matrix; the aging and gypsum removal steps are for curing and forming the final honeycomb material structure. Silane as a modifier can form hydrogen bonds or condense into Si-OR (R is the substrate) with the hydroxyl groups on the surface of the substrate through its hydrolyzed silanol groups, thereby forming a chemical bond between the material and the substrate, significantly improving the bonding effect; in addition, the wet curing reaction of silane does not release CO, which helps to avoid adverse phenomena such as blistering during the curing process and improve the physical and chemical properties of the adhesive, such as bonding strength and heat resistance; diols as modifiers are usually used to adjust the molecular structure of polymers, affecting the flexibility, adhesion and environmental resistance of the material; by introducing diols, the length and crosslinking density of the polymer chain can be changed, thereby optimizing the mechanical properties and processing properties of the material.
[0019] Furthermore, the distance between the plasma generator and the sample is 0.1 to 0.5 cm, and the output power is 50 to 200 W;
[0020] Note: The above parameters can effectively ensure the deposition effect of the honeycomb inorganic material, thereby improving the flame retardancy and durability of the PET composite interlayer.
[0021] Furthermore, the redispersible latex powder comprises, by mass percentage, 50-70% of polyvinyl alcohol emulsion, 3-10% of silicon dioxide, 5-12% of brominated polystyrene, 4-10% of acrylamide and the remainder of shell powder.
[0022] Description: The double helix structure of shell powder can not only provide anti-seepage effect, but also improve the heat resistance and aging resistance of sandwich composite PET foam by enhancing the microstructure and interface bonding force of the composite material; silicon dioxide can be adsorbed on the surface of latex powder particles to reduce the mutual adhesion between particles, thereby maintaining the free flow of powder; acrylamide can form additional chemical cross-linking points in PET foam through chemical reactions. These cross-linking points can increase the intermolecular force of the material, thereby increasing the strength and toughness of the foam. During the high-temperature foaming process, the molecular structure of acrylamide will change, and cross-linking and cyclization reactions will occur with PET chain segments to generate intermolecular imide cross-linking structures and hexaimide ring structures, thereby improving the thermal stability and mechanical properties of the foam; polyvinyl acetate emulsion can improve the frost resistance, low-temperature film-forming properties and water resistance of PET foam, thereby improving the application effect in the marine environment.
[0023] The present invention also provides a method for preparing a sandwich composite PET foam with improved flame retardancy, comprising the following steps:
[0024] S1. Preparation of PET composite interlayer:
[0025] S1-1, heating PET resin particles to 220-260°C to melt them into a liquid state, and then pushing the molten resin to the die head through the screw of the extruder, the extrusion screw speed is 100-300r / min, forming a continuous film, and then cooling in a cooling tank at 0-10°C, mechanically stretching, and heat treating at a temperature of 180-200°C for 1-2h to obtain the PET resin film;
[0026] S1-2, polyethylene terephthalate, polytetrafluoroethylene, and flame retardant are melted and mixed uniformly according to the mass fractions, the mixed materials are added into an autoclave, and then supercritical carbon dioxide liquid is injected to pressurize to 10-15 MPa, and foamed in a glycerol bath at a temperature of 215-230° C., and a flow promoter is added to obtain a foam material;
[0027] S1-3, then spraying the foam material on the PET resin film with a spraying thickness of 0.2 to 0.5 μm, and then compounding the PET resin film and the foam material to obtain a composite base layer, preparing 3 to 5 layers of composite base layers, and compounding each composite base layer in turn by hot melt adhesive to obtain a composite layer, and then subjecting the composite layer to surface anti-reflection treatment to obtain a PET composite interlayer;
[0028] S2. Preparation of top surface layer and anti-seepage bottom surface layer:
[0029] Preparation of the top surface layer: prepare a layered nano carbon black solution and a layered nano aluminum hydroxide solution according to the ratio, then mix the two solutions and add a dispersant to disperse for 15 to 20 minutes under the conditions of ultrasonic power of 100 to 300 W and ultrasonic frequency of 10 to 15 kHz to obtain a dispersion, transfer the dispersion to a hydrothermal reactor, keep it at a temperature of 100 to 240° C. and a pressure of 1 to 3 MPa for 15 to 30 minutes, then push the dispersion to the die head through the screw of the extruder, the extrusion screw speed is 50 to 100 r / min, and cool it at room temperature for 25 to 30 minutes to obtain the top surface layer;
[0030] Preparation of the anti-seepage bottom layer: heating rosin, redispersible latex powder, tourmaline powder, and ethylene-vinyl acetate copolymer according to the weight parts at 120-140° C. for 25-30 minutes to obtain an anti-seepage agent; then using the screw of an extruder to push the anti-seepage agent to a die head, the extrusion screw speed is 50-100 r / min, and cooling at room temperature for 25-30 minutes to obtain an anti-seepage bottom layer;
[0031] S3, sandwich composite
[0032] The top surface layer, the PET composite interlayer and the anti-seepage bottom surface layer are compounded by hot pressing to obtain the interlayer composite PET foam with improved flame retardancy.
[0033] Note: It should be noted that mechanical stretching and heat treatment molding are both processing methods well known to people in the field, and this application does not limit them. People in the field can adjust and select according to actual conditions. Stretching can fix the molecular structure after stretching and improve the dimensional stability of the film. The flow promoter can reduce the viscosity of the material and improve the melt fluidity, so that it can still maintain good foaming performance when adding flame retardants. When preparing PET resin film, the extrusion screw speed is 100-300r / min, and when preparing the top layer and the anti-seepage bottom layer, the extrusion screw speed is 50-100r / min. This is mainly because when the top layer and the bottom layer are foamed, low-speed extrusion helps to improve the overall structural integrity of the foam, reduce the size and number of pores, thereby enhancing its fire resistance, and the high speed in the middle area can improve the mechanical strength of the material, so that the material can still maintain structural integrity in a fire to maintain its flame retardant effect.
[0034] Furthermore, in step S1-2, the foaming is performed in an intermittent foaming manner, that is, the pressure in the autoclave is maintained at 18-23 MPa, the temperature is first raised to 230-250° C., and kept warm for 1-5 minutes to fully melt the formed blend, and then the temperature is reduced to 215-220° C., and kept warm for 1-5 minutes, and then the pressure in the autoclave is released to normal pressure, and then kept warm at 222-228° C. for 1-5 minutes;
[0035] Description: The intermittent foaming process helps to form a more uniform and fine pore structure by controlling the changes in foaming temperature and pressure, which can not only improve the thermal insulation performance of the material, but also improve its mechanical properties because the fine pores can provide better support.
[0036] Further, in step S1-2, the flow promoter is boehmite;
[0037] Description: Boehmite can be used as an effective flow promoter to help improve the fluidity of the blend in the autoclave, thereby ensuring that the material and the expanded graphite material can expand evenly during the foaming process to form a dense foam material. At the same time, it can effectively ensure the flame retardant uniformity of the material. The addition of boehmite can enhance the flexural strength and impact strength of the composite material, which is particularly important for foaming materials because the foaming process may reduce the mechanical properties of the material.
[0038] Furthermore, in step S2, the dispersant is any one of gelatin, methyl cellulose, carboxymethyl cellulose, and polyvinyl pyrrolidone;
[0039] Description: Dispersants are added to improve mixing uniformity, and the nanomaterials in the mixed solution are further dispersed by ultrasonic dispersion or high-speed stirring. These dispersants usually have good biocompatibility and biodegradability, and have little impact on the environment during use.
[0040] Furthermore, it also includes S4, aging treatment, wherein the aging treatment method is: treating at a temperature of 85 to 100° C. and a relative humidity of 25 to 40 RH% for 0.5 to 2 hours, and then cooling in air for 10 to 15 hours to obtain the treated sandwich composite PET foam;
[0041] Description: Ripening can ensure the structural dimensional stability of the foam and prevent deformation and collapse. The above aging steps can promote the release of the foaming agent and the stabilization of the bubbles, which helps to improve the mechanical properties of the foam, thereby improving the compression strength and durability of the foam.
[0042] Furthermore, the sandwich composite PET foam with improved flame retardancy is applied in precision instruments for marine environments.
[0043] Description: The sandwich composite PET foam prepared in this application has good flame retardant effect and excellent moisture resistance and impermeability, which can effectively extend the service life of the sandwich structure, especially in applications such as precision instruments in marine environments that are exposed to harsh environments for a long time.
[0044] Compared with the existing PET foam, the beneficial effects of the present invention are:
[0045] (1) The present invention obtains a composite liquid by mixing nano-cerium oxide particles and a microalgae solution, and then dripping a modifier mixed with silane and a diol, which can control the dispersion and stability of the nano-cerium oxide particles to a certain extent. The honeycomb structure can effectively block the transfer of oxygen and heat and reduce the combustion rate. Inorganic particles usually have high thermal stability and can maintain structural integrity at high temperatures and delay the thermal decomposition of materials. The introduction of nano-cerium oxide particles will increase the hardness and strength of the composite material. At the same time, due to its good thermal stability, the performance of the composite material in a high temperature environment can be improved. The modified composite material also has good wear resistance and corrosion resistance, which can effectively improve the durability and life of the material.
[0046] (2) The sandwich composite PET foam obtained by compounding the top surface layer, the PET composite interlayer and the anti-seepage bottom surface layer of the present invention has good flame retardant properties. It can also prevent moisture penetration in marine environments or other humid conditions through the provision of the anti-seepage bottom surface layer, thereby protecting the core material from the influence of the humid environment, effectively maintaining the integrity and durability of the foam structure. The non-reflective treatment of the surface of the composite layer obtained after compounding the PET resin film and the foam material with equal mass ratio can effectively improve the electromagnetic interference shielding ability of the foam material, thereby optimizing the application effect of the sandwich composite PET foam in the marine environment. DETAILED DESCRIPTION
[0047] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0048] Example 1: A sandwich composite PET foam with improved flame retardancy, which is formed by hot pressing from the outside to the inside in sequence by a top surface layer, a PET composite sandwich layer and an anti-seepage bottom surface layer;
[0049] The top surface layer is compounded by a layered nano carbon black solution with a mass concentration of 40%, a layered nano aluminum hydroxide solution with a mass concentration of 97%, and a dispersant in a ratio of 1:1:0.4;
[0050] The PET composite interlayer is formed by compounding a PET resin film and a foam material in equal weight ratio and then subjecting the composite layer to surface anti-reflection treatment; the foam material comprises, by weight, 90 parts of polyethylene terephthalate, 1.5 parts of polytetrafluoroethylene, 3 parts of a flow promoter, 2 parts of a flame retardant, and 6 parts of glycerol; the flame retardant is a mixture of zinc borate and expanded graphite in a weight ratio of 1:1;
[0051] The method of surface anti-reflection treatment is:
[0052] Preparation of honeycomb inorganic particles: mixing ground nano cerium oxide particles and microalgae solution in a mass ratio of 16:9 to obtain a composite liquid, then mixing silane and diol in a mass ratio of 8:3 to obtain a modifier, adding the modifier accounting for 6 wt.% of the composite liquid to the composite liquid at a rate of 35 mL / min, stirring and hydrolyzing at room temperature for 7 hours, and then casting it into a honeycomb gypsum blank with a through-hole diameter of 2 ppi at a pressure of 0.8 MPa and a pressurizing time of 32 seconds, and removing the gypsum after aging at a temperature of 90°C for 22 hours to obtain honeycomb inorganic particles;
[0053] Surface anti-reflection treatment: honeycomb inorganic particles were deposited on the surface of the composite layer, and then low-temperature plasma curing was performed for 120 seconds under nitrogen atmosphere and 70°C to obtain a PET composite interlayer; the flow rate of the honeycomb inorganic particles was 900 cm 3 / min, deposition rate is 2.4g / min, deposition amount is 65g / dm 2 ; The distance between the plasma generator and the sample is 0.3 cm, and the output power is 120 W;
[0054] The anti-seepage bottom surface layer comprises, by weight: 18 parts of rosin, 5 parts of redispersible latex powder, 3 parts of tourmaline powder, and 33 parts of ethylene-vinyl acetate copolymer;
[0055] The redispersible latex powder comprises, by weight percentage, 60% of polyvinyl alcohol emulsion, 5% of silicon dioxide, 8% of brominated polystyrene, 7% of acrylamide and the balance of shell powder;
[0056] This embodiment also provides a method for preparing a sandwich composite PET foam with improved flame retardancy, comprising the following steps:
[0057] S1. Preparation of PET composite interlayer:
[0058] S1-1, heating PET resin pellets to 240°C to melt them into a liquid state, and then pushing the molten resin to the die head through the screw of the extruder, the extrusion screw speed is 200r / min, forming a continuous film, and then cooling in a cooling tank at 5°C, mechanically stretching, and heat treating at a temperature of 190°C for 1.5h to obtain a PET resin film;
[0059] S1-2, polyethylene terephthalate, polytetrafluoroethylene and flame retardant are melted and mixed uniformly according to the mass fractions, the mixed materials are added into an autoclave, and then supercritical carbon dioxide liquid is injected and pressurized to 13 MPa, a flow promoter is added and foamed in a glycerol bath at a temperature of 222° C. to obtain a foam material; the flow promoter is boehmite;
[0060] S1-3, spraying the foam material on the PET resin film with a spraying thickness of 0.4 μm, and then compounding the PET resin film and the foam material by hot pressing to obtain a composite base layer, preparing 4 layers of composite base layers and compounding them in sequence by hot melt adhesive to obtain a composite layer, and then subjecting the composite layer to surface anti-reflection treatment to obtain a PET composite interlayer; it can be understood that in actual application, the sizes of the PET resin film and the foam material are consistent, and the sizes of the top surface layer, the PET composite interlayer and the anti-seepage bottom surface layer are consistent;
[0061] S2. Preparation of top surface layer and anti-seepage bottom surface layer:
[0062] Preparation of the top surface layer: prepare a layered nano carbon black solution and a layered nano aluminum hydroxide solution in proportion, then mix the two solutions and add a dispersant to disperse for 18 minutes under the conditions of ultrasonic power of 200 W and ultrasonic frequency of 12 kHz to obtain a dispersion, transfer the dispersion to a hydrothermal reactor, keep it at a temperature of 170°C and a pressure of 2MPa for 22 minutes, then push the dispersion to the die head through the screw of the extruder, the extrusion screw speed is 75r / min, and cool it at room temperature for 28 minutes to obtain the top surface layer;
[0063] In step S2, the dispersant is polyvinyl pyrrolidone;
[0064] Preparation of anti-seepage bottom surface layer: rosin, redispersible latex powder, tourmaline powder, and ethylene-vinyl acetate copolymer are heated at 130° C. for 28 minutes according to weight to obtain an anti-seepage agent; then the anti-seepage agent is pushed toward the die head by the screw of an extruder, the extrusion screw speed is 75 r / min, and the anti-seepage bottom surface layer is obtained by cooling at room temperature for 28 minutes;
[0065] S3, sandwich composite
[0066] The top surface layer, the PET composite interlayer and the anti-seepage bottom surface layer are compounded by hot pressing to obtain a sandwich composite PET foam with improved flame retardant performance;
[0067] S4. Ripening
[0068] The aging treatment method is: treating at a temperature of 95° C. and a relative humidity of 32 RH% for 1.2 hours, and then cooling in air for 13 hours to obtain the treated sandwich composite PET foam;
[0069] The present invention also provides an application of the sandwich composite PET foam with improved flame retardancy, and the sandwich composite PET foam with improved flame retardancy is applied to precision instruments for marine environments.
[0070] Embodiment 2: Different from Embodiment 1, the top surface layer is compounded by a layered nano carbon black solution with a mass concentration of 35%, a layered nano aluminum hydroxide solution with a mass concentration of 96%, and a dispersant in a ratio of 1:1:0.3.
[0071] Embodiment 3: Different from Embodiment 1, the top surface layer is compounded by a layered nano carbon black solution with a mass concentration of 45%, a layered nano aluminum hydroxide solution with a mass concentration of 98%, and a dispersant in a ratio of 1:1:0.6.
[0072] Example 4: Different from Example 1, the foam material includes, by weight: 80 parts of polyethylene terephthalate, 0.5 parts of polytetrafluoroethylene, 1 part of flow promoter, 1 part of flame retardant, and 3 parts of glycerol.
[0073] Example 5: Different from Example 1, the foam material includes, by weight: 100 parts of polyethylene terephthalate, 3 parts of polytetrafluoroethylene, 5 parts of flow promoter, 4 parts of flame retardant, and 10 parts of glycerol.
[0074] Example 6: Different from Example 1, honeycomb inorganic particles are prepared: the ground nano cerium oxide particles and the microalgae solution are mixed in a mass ratio of 13:8 to obtain a composite liquid, and then silane and diol are mixed in a mass ratio of 7:1 to obtain a modifier, and the modifier accounting for 5 wt.% of the composite liquid is added dropwise to the composite liquid at a rate of 25 mL / min, stirred and hydrolyzed at room temperature for 5 hours, and then cast into a honeycomb gypsum blank with a through-hole diameter of 0.2 ppi at a pressure of 0.5 MPa and a pressurizing time of 25 seconds, and the gypsum is removed after aging at a temperature of 80°C for 20 hours to obtain honeycomb inorganic particles.
[0075] Example 7: Different from Example 1, honeycomb inorganic particles are prepared: the ground nano cerium oxide particles and the microalgae solution are mixed in a mass ratio of 20:10 to obtain a composite liquid, and then silane and diol are mixed in a mass ratio of 10:4 to obtain a modifier, and the modifier accounting for 7 wt.% of the composite liquid is added dropwise to the composite liquid at a rate of 50 mL / min, stirred and hydrolyzed at room temperature for 10 hours, and then cast into a honeycomb gypsum blank with a through-hole diameter of 5 ppi at a pressure of 1 MPa and a pressurizing time of 40 seconds. After aging at a temperature of 100°C for 24 hours, the gypsum is removed to obtain honeycomb inorganic particles.
[0076] Example 8: Different from Example 1, the surface anti-reflection treatment is as follows: honeycomb inorganic particles are deposited on the surface of the composite layer, and then low-temperature plasma curing is performed for 50 seconds in a nitrogen atmosphere at 50°C to obtain a PET composite interlayer.
[0077] Example 9: Different from Example 1, the surface is anti-reflective treated: honeycomb inorganic particles are deposited on the surface of the composite layer, and then low-temperature plasma curing is carried out for 200 seconds in a nitrogen atmosphere at 90°C to obtain a PET composite interlayer.
[0078] Example 10: Different from Example 1, the flow rate of the honeycomb inorganic particles is 800 cm 3 / min, deposition rate is 1.80g / min, deposition amount is 50g / dm 2 .
[0079] Example 11: Different from Example 1, the flow rate of the honeycomb inorganic particles is 1000 cm 3 / min, deposition rate is 3.50g / min, deposition amount is 80g / dm 2 .
[0080] Example 12: Different from Example 1, the distance between the plasma generator and the sample is 0.1 cm, and the output power is 50 W.
[0081] Example 13: Different from Example 1, the distance between the plasma generator and the sample is 0.5 cm, and the output power is 200 W.
[0082] Example 14: Different from Example 1, the anti-seepage bottom surface layer includes, by mass, 15 parts of rosin, 2 parts of redispersible latex powder, 1 part of tourmaline powder, and 25 parts of ethylene-vinyl acetate copolymer.
[0083] Example 15: Different from Example 1, the anti-seepage bottom surface layer includes, by mass, 20 parts of rosin, 7 parts of redispersible latex powder, 5 parts of tourmaline powder, and 40 parts of ethylene-vinyl acetate copolymer.
[0084] Example 16: Different from Example 1, the redispersible latex powder includes, by mass percentage, 50% polyvinyl alcohol emulsion, 3% silicon dioxide, 5% brominated polystyrene, 4% acrylamide and the remainder shell powder.
[0085] Example 17: Different from Example 1, the redispersible latex powder includes, by mass percentage, 70% polyvinyl alcohol emulsion, 10% silicon dioxide, 12% brominated polystyrene, 10% acrylamide and the remainder shell powder.
[0086] Example 18: Different from Example 1, S1-1, the PET resin particles are heated to 220°C to melt them into a liquid state, and then the molten resin is pushed to the die head by the screw of the extruder. The extrusion screw speed is 100r / min to form a continuous film, which is then cooled in a cooling tank at 0°C.
[0087] Example 19: Different from Example 1, S1-1, the PET resin particles are heated to 260°C to melt them into a liquid state, and then the molten resin is pushed to the die head by the screw of the extruder. The extrusion screw speed is 300r / min to form a continuous film, which is then cooled in a cooling tank at 10°C.
[0088] Example 20: Different from Example 1, in S1-2, supercritical carbon dioxide liquid is injected and pressurized to 10 MPa, a flow promoter is added and foaming is carried out in a glycerol bath at a temperature of 215°C.
[0089] Example 21: Different from Example 1, in S1-2, supercritical carbon dioxide liquid is injected and pressurized to 15 MPa, a flow promoter is added and foaming is carried out in a glycerol bath at a temperature of 230°C.
[0090] Example 22: Different from Example 1, in S1-2, the foaming is carried out in an intermittent foaming manner, that is, the pressure in the autoclave is maintained at 22 MPa, the temperature is first raised to 240°C and kept warm for 3 minutes to allow the formed blend to fully melt, and then the temperature is reduced to 218°C and kept warm for 3 minutes, the pressure in the autoclave is released to normal pressure, and then kept warm at 225°C for 3 minutes; it should be noted that the normal pressure in this embodiment refers to the pressure in the autoclave reaching 0.1 MPa.
[0091] Example 23: Different from Example 22, in S1-2, the pressure in the autoclave is maintained at 18 MPa, the temperature is first raised to 230°C and kept warm for 1 min to allow the molded blend to fully melt, then the temperature is lowered to 215°C and kept warm for 1 min, the pressure in the autoclave is released to normal pressure, and then kept warm at 222°C for 1 min.
[0092] Example 24: Different from Example 22, in S1-2, the pressure in the autoclave is maintained at 23 MPa, the temperature is first raised to 250°C and kept warm for 5 minutes to allow the formed blend to fully melt, then the temperature is lowered to 220°C and kept warm for 5 minutes, the pressure in the autoclave is released to normal pressure, and then kept warm at 228°C for 5 minutes.
[0093] Example 25: Different from Example 22, in S1-3, the foam material is sprayed on the PET resin film with a spraying thickness of 0.2 μm, and then the PET resin film and the foam material are compounded to obtain a composite base layer, and three layers of composite base layers are prepared and the composite base layers are compounded in turn by hot melt adhesive.
[0094] Example 26: Different from Example 22, in S1-3, the foam material is sprayed on the PET resin film with a spraying thickness of 0.5 μm, and then the PET resin film and the foam material are compounded to obtain a composite base layer, and 5 layers of composite base layers are prepared and each composite base layer is compounded in turn by hot melt adhesive.
[0095] Example 27: Different from Example 22, in S2, the temperature is 100°C and the pressure is 1 MPa, and then the dispersion is pushed to the die head by the screw of the extruder, the extrusion screw speed is 50 r / min, and the top layer is obtained by cooling at room temperature for 25 minutes.
[0096] Example 28: Different from Example 22, in S2, the temperature is maintained at 240°C and the pressure is 3 MPa for 30 minutes, and then the dispersion is pushed to the die head by the screw of the extruder, the extrusion screw speed is 100 r / min, and the top layer is obtained by cooling at room temperature for 30 minutes.
[0097] Example 29: Different from Example 22, rosin, redispersible latex powder, tourmaline powder, and ethylene-vinyl acetate copolymer are heated at 120°C for 25 minutes to obtain an anti-seepage agent; then the anti-seepage agent is pushed toward the die head by the screw of the extruder, the extrusion screw speed is 50r / min, and the mixture is cooled at room temperature for 25 minutes to obtain an anti-seepage bottom layer.
[0098] Example 30: Different from Example 22, rosin, redispersible latex powder, tourmaline powder, and ethylene-vinyl acetate copolymer are heated at 140°C for 30 minutes to obtain an anti-seepage agent; then the anti-seepage agent is pushed toward the die head by the screw of the extruder, the extrusion screw speed is 100r / min, and the mixture is cooled at room temperature for 30 minutes to obtain an anti-seepage bottom layer.
[0099] Example 31: Different from Example 22, the aging treatment method is: treating at a temperature of 85°C and a relative humidity of 25RH% for 0.5h, and then cooling in air for 10h to obtain the treated sandwich composite PET foam.
[0100] Example 32: Different from Example 22, the aging treatment method is: treating at a temperature of 100°C and a relative humidity of 40RH% for 2 hours, and then cooling in air for 15 hours to obtain the treated sandwich composite PET foam.
[0101] Experimental Example: In order to illustrate the flame retardant properties of the sandwich composite PET foam prepared by the present invention, the following experiment was designed:
[0102] Flame retardant effect test: In this experiment, a horizontal vertical combustion tester was used to test the flame retardant samples, and the flame retardant grade was classified according to the UL94V-0 standard. The tested samples meet the standard technical indicators, which require the ignition distance of the sample to be 150mm, the blue flame height to be 20mm+2mm, the sample size to be 125mm±5mm in length, 13.0mm+0.3mm in width, and 3.0mm+0.2mm in thickness. The gas used is methane. During the test, one end of the prepared standard sample was fixed on the vertical fixture, and the other end was exposed to the specified test flame. The vertical burning behavior of the sample was evaluated by observing and recording the burning time, the dripping of the burning particles, and whether the absorbent cotton was burning, and classified according to the UL94V-0 standard. During the test, 5 sample strips were prepared for each group, and the measurements were taken multiple times to calculate the average value. In addition, absorbent cotton was placed 12cm below the lower end of the sample, the flame height was adjusted to 20mm, the flame was continuously applied to the sample for 10 seconds, and then the flame was withdrawn. The sample is subjected to two 10-second combustion tests. The flame goes out within 10 seconds and no burning material can fall. It is rated as V0. The sample is subjected to two 10-second combustion tests. The flame goes out within 30 seconds. Burning materials can fall, but the cotton wool at the bottom of the sample cannot be ignited. It is rated as V1. The sample is subjected to two 10-second combustion tests. The flame goes out within 30 seconds. Burning materials can fall, and the dripping materials are allowed to ignite the cotton wool. It is rated as V2. The sample is not allowed to burn onto the fixture in each combustion.
[0103] Thermal insulation test method: Refer to QB / T 8045-2024 standard to test the thermal insulation performance of polyethylene terephthalate (PET) structural foam;
[0104] The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.
[0105] 1. Explore the influence of the composition of sandwich composite PET foam on the performance of sandwich composite PET foam
[0106] Comparative Example 1: Different from Example 1, the composite layer is not subjected to surface anti-reflection treatment.
[0107] Comparative Example 2: Different from Example 1, the composite liquid is not modified during the anti-reflection treatment.
[0108] Control Example 3: Different from Example 1, the redispersible latex powder does not contain shell powder.
[0109] Table 1 Effect of the composition of sandwich composite PET foam on the properties of sandwich composite PET foam
[0110]
[0111] Conclusion: By comparing Examples 1 to 5, Examples 8 to 13 and Control Example 1, it can be seen that the anti-reflection treatment has a relatively small effect on the flame retardant effect of the foam, but this step can significantly enhance its thermal insulation performance by increasing the reflectivity of the material and reducing the heat loss through radiation, thereby further improving the thermal insulation effect of the PET foam; By comparing Examples 1, Examples 6 to 7 and Control Example 2, it can be seen that the modification of the composite liquid with a modifier can help the nano-cerium oxide particles to be more effectively embedded in the honeycomb gypsum matrix, thereby effectively preparing the honeycomb non-polar particles, and the use of a special porous structure liquid can effectively scatter light and reduce surface reflection, thereby further optimizing the thermal insulation effect of the sandwich composite PET foam; By comparing Examples 1, Examples 14 to 17 and Control Example 3, it can be seen that the addition of shell powder also has a positive effect on improving the flame retardant and thermal insulation properties of the sandwich composite PET foam, because the double helix structure of the shell powder can not only provide an anti-seepage effect, but also enhance the microstructure and interface bonding strength of the composite material, thereby improving the heat resistance and aging resistance of the sandwich composite PET foam.
[0112] 2. Investigate the effect of the preparation method of sandwich composite PET foam on its performance
[0113] Control Example 4: Different from Example 1, the extrusion screw speed during step S1-1, preparation of the top surface layer, and preparation of the anti-seepage bottom surface layer is 75 r / min.
[0114] Comparative Example 5: Different from Example 1, in step S1-2, the flow promoter is 80T.
[0115] Table 2 Effect of the preparation method of sandwich composite PET foam on the properties of sandwich composite PET foam
[0116] Group Example 1 Example 8 Example 9 Embodiment 18 Embodiment 19 Flame retardant grade V0 V1 V1 V1 V1 Thermal conductivity W / m·K 0.08 0.09 0.12 0.11 0.09 Group Embodiment 20 Embodiment 21 Embodiment 22 Embodiment 23 Embodiment 24 Flame retardant grade V1 V1 V0 V0 V0 Thermal conductivity W / m·K 0.09 0.08 0.04 0.06 0.05 Group Embodiment 25 Embodiment 26 Embodiment 27 Embodiment 28 Embodiment 29 Flame retardant grade V0 V0 V0 V0 V0 Thermal conductivity W / m·K 0.05 0.04 0.05 0.05 0.04 Group Embodiment 30 Embodiment 31 Embodiment 32 Comparative Example 4 Comparative Example 5 Flame retardant grade V0 V0 V0 V1 V0 Thermal conductivity W / m·K 0.05 0.05 0.06 0.10 0.15
[0117] Conclusion: From the data comparison of Example 1, Examples 8 to 9 and Control Example 4, it can be seen that if the extrusion screw speed is not specified in the present application or the flow promoter is a commercially available 80T, the performance of the sandwich composite PET foam will deteriorate. The reason why the flame retardant and thermal insulation effects of the PET resin film prepared in Example 1 are better is mainly because low-speed extrusion can help improve the overall structural integrity of the foam and reduce the size and number of pores when foaming the top and bottom layers, thereby enhancing its fire resistance, while the high speed in the middle area can improve the mechanical strength of the material, so that the material can still maintain its structural integrity in a fire to maintain its flame retardant effect; and from the comparison of Example 1, Examples 8 to 9 and Examples 18 to 30, it can be seen that Examples 22 to 30 have obvious performance improvements compared with Examples 1 to 21, mainly because the intermittent foaming process can be controlled by The changes in the foaming temperature and pressure are helpful to form a more uniform and fine pore structure, thereby improving the thermal insulation performance of the material and ensuring its thermal insulation effect; and the data comparison of Example 1, Examples 20-21 and Control Example 5 shows that although the flow promoter 80T can also meet the flame retardant effect, the thermal insulation performance is poor; this is because the flow promoter 80T will affect the formation and stability of the foam, but the addition of boehmite may provide additional nucleation points, which is helpful to form a more uniform foam structure, while increasing the rigidity and thermal stability of the material. Boehmite can be used as an effective flow promoter to help improve the fluidity of the blend in the autoclave. Compared with 80T, the addition of boehmite can also enhance the bending strength and impact strength of the composite material, which can compensate for the fact that the foaming process may reduce the mechanical properties of the material, thereby optimizing its thermal insulation performance.
Claims
1. A sandwich composite PET foam with improved flame retardancy, characterized in that: From the outside to the inside, it is composed of a top surface layer, a PET composite interlayer and an anti-seepage bottom surface layer through hot pressing molding. The top surface layer is compounded by a layered nano carbon black solution with a mass concentration of 35-45%, a layered nano aluminum hydroxide solution with a mass concentration of 96-98%, and a dispersant in a ratio of 1:1:0.3-0.6; The PET composite interlayer is formed by a composite layer obtained by compounding a PET resin film and a foam material in equal mass ratios and then undergoing surface anti-reflection treatment; the foam material comprises, by weight: 80 to 100 parts of polyethylene terephthalate, 0.5 to 3 parts of polytetrafluoroethylene, 1 to 5 parts of a flow promoter, 1 to 4 parts of a flame retardant, and 3 to 10 parts of glycerol; the flame retardant is a mixture of zinc borate and expanded graphite in a mass ratio of 1:1; The anti-seepage bottom surface layer comprises, by weight, 15 to 20 parts of rosin, 2 to 7 parts of redispersible latex powder, 1 to 5 parts of tourmaline powder, and 25 to 40 parts of ethylene-vinyl acetate copolymer.
2. A sandwich composite PET foam with improved flame retardancy as claimed in claim 1, characterized in that: The method of the surface anti-reflection treatment is: Preparation of honeycomb inorganic particles: mixing ground nano cerium oxide particles and microalgae solution in a mass ratio of 13-20:8-10 to obtain a composite liquid, then mixing silane and diol in a mass ratio of 7-10:1-4 to obtain a modifier, adding 5-7wt.% of the modifier to the composite liquid at a rate of 25-50mL / min, stirring and hydrolyzing at room temperature for 5-10h, and then casting into a honeycomb gypsum blank with a through-hole diameter of 0.2-5ppi at a pressure of 0.5-1MPa and a pressurizing time of 25-40s, aging at a temperature of 80-100°C for 20-24h, and then removing the gypsum to obtain honeycomb inorganic particles; Surface anti-reflection treatment: honeycomb inorganic particles are deposited on the surface of the composite layer, and then low-temperature plasma curing is performed for 50 to 200 seconds under a nitrogen atmosphere at 50 to 90°C to obtain a PET composite interlayer; the flow rate of the honeycomb inorganic particles is 800 to 1000 cm 3 / min, deposition rate is 1.80~3.50g / min, deposition amount is 50~80g / dm 2 .
3. A sandwich composite PET foam with improved flame retardancy as claimed in claim 2, characterized in that: The distance between the plasma generator and the sample is 0.1-0.5 cm, and the output power is 50-200W.
4. The sandwich composite PET foam with improved flame retardancy as claimed in claim 1, characterized in that: The redispersible latex powder comprises, by mass percentage, 50-70% of polyvinyl alcohol emulsion, 3-10% of silicon dioxide, 5-12% of brominated polystyrene, 4-10% of acrylamide and the remainder of shell powder.
5. A method for preparing a sandwich composite PET foam with improved flame retardancy as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Preparation of PET composite interlayer: S1-1, heating PET resin particles to 220-260°C to melt them into a liquid state, and then pushing the molten resin to the die head through the screw of the extruder, the extrusion screw speed is 100-300r / min, forming a continuous film, and then cooling in a cooling tank at 0-10°C, mechanically stretching, and heat treating at a temperature of 180-200°C for 1-2h to obtain the PET resin film; S1-2, polyethylene terephthalate, polytetrafluoroethylene, and flame retardant are melted and mixed uniformly according to the mass fractions, the mixed materials are added into an autoclave, and then supercritical carbon dioxide liquid is injected to pressurize to 10-15 MPa, and foamed in a glycerol bath at a temperature of 215-230° C., and a flow promoter is added to obtain a foam material; S1-3, spraying the foam material on the PET resin film with a spraying thickness of 0.2 to 0.5 μm, and then compounding the PET resin film and the foam material to obtain a composite base layer, preparing 3 to 5 layers of composite base layers, and compounding the composite base layers in sequence by hot melt adhesive to obtain a composite layer, and then subjecting the composite layer to surface anti-reflection treatment to obtain a PET composite interlayer; S2. Preparation of top surface layer and anti-seepage bottom surface layer: Preparation of the top surface layer: prepare a layered nano carbon black solution and a layered nano aluminum hydroxide solution according to the ratio, then mix the two solutions, add a dispersant, and disperse for 15 to 20 minutes under the conditions of an ultrasonic power of 100 to 300 W and an ultrasonic frequency of 10 to 15 kHz to obtain a dispersion, transfer the dispersion to a hydrothermal reactor, keep it at a temperature of 100 to 240° C. and a pressure of 1 to 3 MPa for 15 to 30 minutes, then push the dispersion to the die head through the screw of the extruder, the extrusion screw speed is 50 to 100 r / min, and cool it at room temperature for 25 to 30 minutes to obtain the top surface layer; Preparation of the anti-seepage bottom layer: heating rosin, redispersible latex powder, tourmaline powder, and ethylene-vinyl acetate copolymer according to the weight parts at 120-140° C. for 25-30 minutes to obtain an anti-seepage agent; then using the screw of an extruder to push the anti-seepage agent to a die head, the extrusion screw speed is 50-100 r / min, and cooling at room temperature for 25-30 minutes to obtain an anti-seepage bottom layer; S3, sandwich composite The top surface layer, the PET composite interlayer and the anti-seepage bottom surface layer are compounded by hot pressing to obtain the interlayer composite PET foam with improved flame retardancy.
6. The method for preparing a sandwich composite PET foam with improved flame retardancy as claimed in claim 5, characterized in that: In step S1-2, the foaming is performed in an intermittent foaming manner, that is, the pressure in the autoclave is maintained at 18 to 23 MPa, the temperature is first raised to 230 to 250° C., and kept warm for 1 to 5 minutes to fully melt the formed blend, and then the temperature is reduced to 215 to 220° C., and after keeping warm for 1 to 5 minutes, the pressure in the autoclave is released to normal pressure, and then kept warm at a temperature of 222 to 228° C. for 1 to 5 minutes.
7. The method for preparing a sandwich composite PET foam with improved flame retardancy as claimed in claim 5, characterized in that: In step S1-2, the flow promoter is boehmite.
8. The method for preparing a sandwich composite PET foam with improved flame retardancy as claimed in claim 5, characterized in that: In step S2, the dispersant is any one of gelatin, methyl cellulose, carboxymethyl cellulose, and polyvinyl pyrrolidone.
9. The method for preparing a sandwich composite PET foam with improved flame retardancy as claimed in claim 5, characterized in that: The method further includes S4, aging treatment, wherein the aging treatment is carried out at a temperature of 85-100° C. and a relative humidity of 25-40 RH% for 0.5-2 hours, and then cooled in air for 10-15 hours to obtain the treated sandwich composite PET foam.
10. The use of the sandwich composite PET foam with improved flame retardancy as claimed in claim 5, characterized in that: The sandwich composite PET foam with improved flame retardancy is applied in precision instruments for marine environments.
Citation Information
Patent Citations
High-flame-retardance composite heat-insulating foam material and preparation method thereof
CN103059336A
PET sandwich composite flame-retardant insulation board
CN212002034U